The effect of photoinduced surface oxygen vacancies on the charge carrier dynamics in TiO2 films - Dagdeviren,OE; Glass,D; Sapienza,R; Cortes,E; Maier,SA; Parkin,IP; Grutter,P; Quesada-Cabrera,R (Nano Letters: a journal dedicated to nanoscience and nanotechnology, 2021)
Metal-oxide semiconductors (MOS) are widely utilized for catalytic and photocatalytic applications in which the dynamics of charged carriers (e.g., electrons, holes) play important roles. Under operation conditions, photoinduced surface oxygen vacancies (PI-SOV) can greatly impact the dynamics of charge carriers. However, current knowledge regarding the effect of PI-SOV on the dynamics of hole migration in MOS films, such as titanium dioxide, is solely based upon volume-averaged measurements and/or vacuum conditions. This limits the basic understanding of hole-vacancy interactions, as they are not capable of revealing time-resolved variations during operation. Here, we measured the effect of PI-SOV on the dynamics of hole migration using time-resolved atomic force microscopy. Our findings demonstrate that the time constant associated with hole migration is strongly affected by PI-SOV, in a reversible manner. These results will nucleate an insightful understanding of the physics of hole dynamics and thus enable emerging technologies, facilitated by engineering hole-vacancy interactions.